Bacillus Calmette–Guérin Infection and Cytotoxicity in the Retinal Pigment Epithelium. (4th July 2018) - Llorenç, Victor; Mesquida, Marina; Molins, Blanca; González-Martín, Julián; Sainz de la Maza, Maite; Adán, Alfredo
ABSTRACT: Purpose : To investigate bacillus Calmette–Guérin (BCG) infective capability and cytotoxicity in ARPE-19 cells. Methods : BCG inoculum was dispensed at a MOI 100:1 for 3 h in 90% confluent ARPE-19 cells. Infection rates at different time points were determined by colony forming units (CFU) count and, in parallel, by the number of microscopically infected cells. WST-1 reagent was used for cytotoxicity assays. Results : A 67-year-old man previously treated with intravesical BCG for bladder carcinoma presented with chronic, refractory, bilateral uveitis with macular edema. Quiescence was achieved only after commencing antituberculous treatment. BCG infection rate by two methods peaked at 48 h (16 ± 5.7% by CFU count and 40 ± 7.7% by microscopy; p = 0.058). BCG adhesion, phagocytosis, intracellular proliferation and cytolysis was observed. Cytotoxicity was minimal and did not differ from uninfected cells. Conclusions : BCG can infect at low rates and proliferate in ARPE-19 cells without toxicity in the surrounding monolayer.